TEACHERS’ PARALANGUAGE IN CLASSROOM INTERACTION - Anindya Anisa Ayuningsih; Murni Mahmud; Kisman Salija; Maemuna Muhayyang (Universitas Negeri Makassar, 2022)
Paralanguage, as a part of non-verbal communication, is believed to have fruitful contribution to the successful teaching and learning process. Therefore, it is crucial to explore the features of teachers’ paralanguage in EFL classroom interactions and the function of those paralanguage features in classroom interaction. Under the design of qualitative research, this study employed classroom observation and recording. The subject is one English class with one teacher and 31 students in one Senior High School in Makassar, Indonesia. To analyze data, steps of analysis which included data collection, data reduction, data display and conclusion (drawing or verifying) adopted from Miles, Huberman, and Saldana (2014) were employed. The result of data analysis showed that the teacher applied some features of paralanguage in classroom interaction in the forms of (1) voice qualities that consist of pitch (the highness and lowness of tone), rhythm (smooth rhythm), and rate (slow rate or tempo); and (2) vocalizations that include vocal characterizers (laughing) and vocal segregate (sound “ee”). This study also found that the use of teacher’s paralanguage in teaching was (1) to accent, (2) to complement, (3) to contradict, (4) to regulate, and (5) to repeat. Findings from this study can become a reference for teachers in creating effective classroom interaction. The use of paralanguage by the teacher in the class as one aspect of non-verbal communication is needed as one way to create effective classroom interaction.